Manajemen Kurikulum Merdeka dalam Meningkatkan Mutu Pembelajaran Seni Budaya di SDN 22 Talang Kelapa - Saodah, Saodah; Putra, Alhadi Yan; Rosani, Meilia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study investigates the management of the Merdeka Curriculum in enhancing the quality of arts and culture learning at SDN 22 Talang Kelapa, a designated Sekolah Penggerak (Driving School). The research aims to explore the implementation process of curriculum management, identify challenges faced by educators, and propose solutions to overcome these issues. Utilizing a qualitative descriptive approach with data triangulation, researchers collected information through structured interviews, direct observations, and documentation. Participants included school principals, teachers, students, and school committee members. The results reveal that the planning and implementation of the Merdeka Curriculum were carried out effectively through diagnostic assessments, differentiated instruction, and reflective teaching practices. The integration of the Projek Penguatan Profil Pelajar Pancasila (P5) promoted students’ character building, creativity, and engagement in cross-subject learning. However, some obstacles remain, particularly related to limited digital infrastructure, insufficient experience among newly assigned teachers, and incomplete teaching modules on the official platform. To address these issues, the school conducted ongoing professional development programs and fostered collaborative practices among stakeholders. This research underscores the importance of structured curriculum management and sustained teacher support to ensure the successful implementation of the Merdeka Curriculum, ultimately improving the quality of arts and culture education in primary schools.